Pharmacokinetic Variability of Direct Oral Anticoagulants and Calcium Channel Blockers: A Comparative Analysis of Exposure Data from Clinical Studies - Lara Marques; Nuno Vale (Pharmaceutics, 2026)
Background/Objectives: Interindividual pharmacokinetic (PK) variability remains a daunting challenge for effective and safe drug therapy. Despite the widespread use of direct oral anticoagulants (DOACs) and calcium channel blockers (CCBs), a substantial number of adverse drug reactions have been reported for both classes. Herein, this study aimed to assess and analyze the PK variability of DOACs and CCBs across diverse clinical and demographic profiles under both single- and multiple-dose conditions. Methods: A PubMed search identified clinical PK studies reporting maximum plasma concentration (Cmax) and/or area under the concentration-time curve (AUC). The coefficient of variation (CV%) was calculated and used as a measure of PK variability. A CV% < 40% indicated low-to-moderate variability, and a CV% > 40% was defined as high variability. Results: A total of 264 studies were included following systematic screening, and the dataset was further characterized according to population features and clinical context. Among DOACs, edoxaban exhibited the lowest PK variability, whereas dabigatran showed the highest. CCBs demonstrated a broad variability spectrum, ranging from predictable agents (amlodipine and felodipine) to highly variable compounds (nisoldipine, isradipine, nimodipine, diltiazem, and verapamil). Studies evaluating drug–drug interactions, ethnicity, and specific drug-related factors were associated with increased PK variability. Conclusions: These findings suggest that fixed-dose strategies may not be universally appropriate for DOACs and CCBs, particularly in high-risk subgroups where altered exposure may lead to sub- or supratherapeutic concentrations and compromise clinical outcomes. Therefore, clinicians should avoid evaluating individual risk factors in isolation and instead consider the patient’s complete profile when selecting and adjusting pharmacotherapy.